Offshore Banking : An Analysis of Micro- and Macro-Prudential Issues - Errico, Luca (IMF Working Papers; Working Paper ;, 1999)
The paper takes a closer look at offshore banking-a pervasive practice that has played a role in recent crises. Offshore banking is an increasingly attractive alternative to the sometimes heavily regulated financial markets of emerging economies. From a microeconomic vantage point, offshore banks seem to exploit the risk-return tradeoff by being more profitable than onshore banks, and in many instances also more leveraged. Risks stemming from offshore activities may be easily transmitted onshore with systemic consequences. Current prudential and supervisory frameworks are broadly adequate for risk management if effectively and universally implemented.